Integrating Islamic Business Ethics Into Retail Marketing Strategies: A Case Study Of Sakinahmart Surabaya - Raditya Hasan; Muhammad Alfan Rumasukun; Rusyda Afifah Ahmad; Meichio Lesmana (Yayasan Darussalam Patalassang, 2026)
This research examines the integration of Islamic business ethics into marketing strategies at Sakinahmart, using qualitative research and a case study approach. The 7Ps of marketing mix (product, price, place, promotion, people, process, and physical evidence) are used as an analytical framework to identify the implementation of Islamic business ethics in marketing strategies. Data was obtained through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion techniques. The results show that Sakinahmart consistently integrates Islamic business ethics values into all of its marketing strategies. The sale of products is guaranteed to be halal with halal certification. Pricing is determined transparently, fairly, and without price monopolies. Product distribution is carried out while maintaining halal compliance and avoiding hoarding. Promotions are conducted honestly, without exaggeration or misleading consumer information. Human resources at Sakinahmart practices ethical behavior and provides fair wages and compensation. Operational processes follow Sharia standards and utilize Sharia financial services. Physical evidence of this integration is reflected in the provision of worship facilities and an Islamic store atmosphere. This integration contributes to increased consumer loyalty and strengthens retail competitiveness in Surabaya.